Performances negras e homoeróticas na literatura de James Baldwin - Bezerra, Paulo Rogério Bentes (2020)
The aim of this academic paper is to discuss, primarily, the homoeroticism and the negritude in the literature produced by James Baldwin, with the focus on Performances Culturais.The homoeroticism is discussed under the conception that the sexuality of the main male characters of both novels is not fixed, stable, but undefined, in transit and performative. The masculinity and the space are also issues within this literary scope of black and homoerotic bodies, particularly in the narrative of the novels Another Country and Just Above My Head, written by James Baldwin. Both novels are discussed in this work throughout the idea of an anti-hegemonic masculinity, in which the virility is not attached to heteronormativity but to a whole set of sexual ambiguity, regarding the main male characters. In terms of the space matter, this research carries the idea that it is intertwined with the characters, through their peripheric aspect, indoors and outdoors. The narratives take place in neighborhoods which are located in the margins of New York City. Furthermore, the city communities, their places of social interaction and the ideology of racial segregations are issues of discussion and lead to a complex urban performance in the writing by Baldwin. Moreover, African American Literature brings out the discussion of Escrevivência, a literary term created by Brazilian black female writter Conceição Evaristo. This term is viewed in this research as object of an approximation between the literature of James Baldwin and Conceição Evaristo. Finally, in order to better conduct his academic paper, I selected as theoretical framework, the works of bell hooks (1992, 2015), Paul Gilroy (2007), Kimberlé Crenshaw (1989), Grada Kilomba (2019), Gaston Bachelard (1984), Fernando Seffner (2016), Jurandir Freire Costa (1992, 1995), Toni Morrison and Conceição Evaristo (1996) among other contributions.